An investigation into vibration-induced fatigue failure of metro vehicle cowcatcher and its structural improvement design. (March 2023) - Liu, Yang; Wu, Xingwen; Liu, Kaicheng; Tao, Gongquan; Wen, Zefeng; Zhou, Yabo; Xie, Chenxi; Yang, Ningrui; Gao, Aolin; Zhang, Zhenxian; Hou, Jianwen
Highlights: Based on a large number of field tests and investigations, the root cause of the failure of the cowcatcher was found. Through theoretical derivation and numerical simulation, a modal difference frequency design method is proposed. A random vibration model was proposed instead of the full-scale rigid-flexible coupled dynamic model of the vehicle system. The improved structure of the cowcatcher effectively prolongs the fatigue life and meets the design requirements. Abstract: Cowcatchers are used in metro vehicles to remove obstacles on the track. The failure of the cowcatcher will seriously affect the safety and reliability of the train. This paper investigated the fatigue failure of cowcatchers of metro vehicles induced by the high frequency vibration through both field tests and numerical simulations. The dynamic stress, acceleration, and eigenmode of a cowcatcher as well as the wheel out-of-roundness (OOR) were measured to identify the primary factor of the fatigue failure of cowcatchers. The investigation results indicate that the main cause of the premature fatigue fracture of cowcatchers is the first-order bending eigenmode of the cowcatcher (95.4 Hz) excited by rail corrugation with the passing frequency of approximately 95 Hz. A modal differential frequency design method was proposed to improve the design of cowcatcher. The first-order natural mode frequency of the re-designed cowcatcher increases from 95.4 Hz to 160 Hz, which can effectively avoid the serious vibration excited by rail corrugation. Subsequently, a random vibration model was proposed to evaluate the effects of the improved cowcatcher. The acceleration measured in the field was used as the input of the model to reproduce the vibration environment of the cowcatcher. The model was validated by the measurement result of dynamic stress of the original cowcatcher. The fatigue life of the improved cowcatcher was calculated by the model. Compared with the original cowcatcher, the service life of the improved cowcatcher is greatly improved.